2013
DOI: 10.1002/esp.3421
|View full text |Cite
|
Sign up to set email alerts
|

Shear velocity estimates in rough‐bed open‐channel flow

Abstract: Shear velocity u * is an important parameter in geophysical flows, in particular with respect to sediment transport dynamics. In this study, we investigate the feasibility of applying five standard methods [the logarithmic mean velocity profile, the Reynolds stress profile, the turbulent kinetic energy (TKE) profile, the wall similarity and spectral methods] that were initially developed to estimate shear velocity in smooth bed flow to turbulent flow over a loose bed of coarse gravel (D 50 = 1Á5 cm) under sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 36 publications
4
35
0
1
Order By: Relevance
“…Suitability of this method was demonstrated by Mrokowska et al (2016) in selected experimental datasets. This paper confirmed that the results of Savitzky-Golay filter were compatible with those obtained by approximating the data with a difference quotient and then by Fourier Transform filtering that is very popular in unsteady flow data smoothing (Bagherimiyab and Lemmin, 2013;Rowiński and Czernuszenko, 1998;Song and Graf, 1996). Nonetheless, in this case, Savitzky-Golay filter appeared to be superior to the other one thanks to its straightforward application; it also produced much fewer oscillations.…”
Section: Data Processing and Analysis Evaluation Of Bedload Transportsupporting
confidence: 84%
“…Suitability of this method was demonstrated by Mrokowska et al (2016) in selected experimental datasets. This paper confirmed that the results of Savitzky-Golay filter were compatible with those obtained by approximating the data with a difference quotient and then by Fourier Transform filtering that is very popular in unsteady flow data smoothing (Bagherimiyab and Lemmin, 2013;Rowiński and Czernuszenko, 1998;Song and Graf, 1996). Nonetheless, in this case, Savitzky-Golay filter appeared to be superior to the other one thanks to its straightforward application; it also produced much fewer oscillations.…”
Section: Data Processing and Analysis Evaluation Of Bedload Transportsupporting
confidence: 84%
“…In this table, represents the cross section at which the measurement is carried out, L the distance from the outer bank, R the radial distance from the bend center, and X and Y the coordination of the points in x-and y-directions in Cartesian system sequentially. It can be seen at some points in the field (e.g., B, D, F, I, S, U, W, Z, Bagherimeyab et al (2008), and Bagherimiyab and Lemmin (2013) have conducted studies on the difference in the Reynolds shear stress method at two different layers near the bed by investigating straight channels, and hence reported an increase in bed shear stress from water surface to bed; Whereas, it was observed that the deeper the depth from the bed, the greater the Reynolds stress. According to the data given in Table 2, in most of the presented points (note the stress values at H, K, M, N, O, Q, R, T, V, X, HA, KA, and QA Points), the bed shear stress distribution in the 180 degree sharp bend in depth has either become disorderly or experienced increased shear stress.…”
Section: Bed Shear Stress Distribution Along the 180 Degreementioning
confidence: 94%
“…In some studies, τe is deduced from local values of bed shear stress τl, which are generally computed from the velocity or turbulent profiles obtained with ADV or PIV measurements (Biron et al. ; Bagherimiyad and Lemmin, ). These measurements are time consuming and not adapted for experiments in unsteady flows.…”
Section: Methodsmentioning
confidence: 99%